The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3390/ma9060410
|View full text |Cite
|
Sign up to set email alerts
|

Design of Inorganic Polymer Mortar from Ferricalsialic and Calsialic Slags for Indoor Humidity Control

Abstract: Amorphous silica and alumina of metakaolin are used to adjust the bulk composition of black (BSS) and white (WSS) steel slag to prepare alkali-activated (AAS) mortars consolidated at room temperature. The mix-design also includes also the addition of semi-crystalline matrix of river sand to the metakaolin/steel powders. The results showed that high strength of the steel slag/metakaolin mortars can be achieved with the geopolymerization process which was particularly affected by the metallic iron present into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…However, the final material has still a composite microstructure with a matrix phase having a gel structure where coarse aggregates of unreacted phases are distributed. Their quantities and distribution are parameters that favor the optimization of material properties [50,51]. Since larger zones of the matrix phase are detrimental to strength, this work show that a limited fraction of a heat-treated laterite must be added (30 wt% of LN500) to attain a value of 18.25 MPa that meets the standard mechanical strength [52].…”
Section: Discussionmentioning
confidence: 80%
“…However, the final material has still a composite microstructure with a matrix phase having a gel structure where coarse aggregates of unreacted phases are distributed. Their quantities and distribution are parameters that favor the optimization of material properties [50,51]. Since larger zones of the matrix phase are detrimental to strength, this work show that a limited fraction of a heat-treated laterite must be added (30 wt% of LN500) to attain a value of 18.25 MPa that meets the standard mechanical strength [52].…”
Section: Discussionmentioning
confidence: 80%
“…These absorptions have been attributed to both atmospheric and bound water in geopolymers. 10,11 The bands at 1424 cm -1 and 878 cm -1 point to carbonate presence. 12 This is probably caused by the reaction of atmospheric CO 2 with calcium hydroxide (band at »878 cm -1 ) (sample GPRM1 and sample GPRM2).…”
Section: Ftir Analysismentioning
confidence: 99%
“…Some authors reported that geopolymers are focused on the behavior of Si-O-Si and Si-O-Al bands. [10][11][12][13] Taking a straightforward approach, the identification of the position of the main Si-O-T (T=Si or Al) asymmetric stretching vibration (the strongest band) is here defined as the point of maximum absorbance in the region 1250-950 cm -1 and at 420-500 cm -1 . These peaks will be referred to as the "main band" in the spectrum of the geopolymers.…”
Section: Ftir Analysismentioning
confidence: 99%
“…This might suggest the formation of some new sixfold-coordinated ferric sites most probably located at amorphous gel-like phases 40 . These amorphous iron-rich phases have different structural characteristics than the typical aluminosilicate structure of the geopolymer gel, and certainly the presence of iron into the adhesive bonds influences the overall strength of the geopolymer composite 41 . www.nature.com/scientificreports/ Leachability.…”
mentioning
confidence: 99%